(untitled) (Proceedings of the International Conference on Gender and Sexuality, 2023)
Women’s empowerment is one of the global priority agendas. Qina Mbokodo (QM) is a group of women living and working on farms in the uMgungundlovu District of KwaZulu-Natal. QM mobilises and advocates for women’s land and labour rights through a series of activities, including empowerment; women claiming their rights; shaping decisions, policies and processes that affect their lives; and holding power to account by challenging systems that perpetuate poverty and inequality. This is in line with Goal 2 of the United Nations’ Sustainable Development Goals, which explicitly mentions addressing the nutritional needs of women and adolescent girls and the constraints facing women. Small-scale food producers’ poverty remains a persistent contributing factor to gender inequality, particularly for young girls and women residing within the farms of the uMgungundlovu area, which is also among the reasons why women are often rendered vulnerable as victims of exploitation. This organisation (QM) allows all women who live on farms or are labour tenants to speak out and voice their issues to policy-makers. The purpose of this paper is to document the formation of QM and to describe how the organisation is assisting women labour tenants to get justice and service delivery. The material for the paper is based on focus group discussions with QM members, the Association for Rural Advancement Land Rights Advocacy (AFRA) and the Office of the Special Master. The main finding from our qualitative study speaks to women’s empowerment through gaining knowledge about their rights and how to exercise them. Through this knowledge gained from QM, women have accessed social security benefits such as social grants and improved basic services.